Professores iniciantes de educação física: experiências da formação inicial - Graciele Stolarski; Arestides Pereira da Silva Junior; Alvori Ahlert; Adelar Aparecido Sampaio (Universidade Estadual do Oeste do Paraná, 2019)
Objetivo: Apresentar as vivências da formação inicial de professores iniciantes de Educação Física. Métodos: O estudo é de cunho qualitativo, de caráter descritivo com abordagem e delineamento transversal, no qual participaram seis professores de Educação Física iniciantes na carreira. Como instrumento de coleta, utilizou-se a entrevista semiestruturada, com tratamento de análise de conteúdo. Resultados: Os principais resultados mostram a valorização das disciplinas de formação educacional e estágio curricular supervisionado, discrepâncias entre formação e contexto escolar e as influências das situações adversas como elementos desafiadores no início da docência. A motivação e o desejo de permanecer na profissão revelam elementos de percepção positiva de eficácia profissional. Conclusão: Conclui-se que os professores de Educação Física iniciantes sentem-se motivados para docência, embora a vivência desafiadora do choque com a realidade. Sugere-se o apoio à inserção na carreira, bem como para a permanência na profissão. ABSTRACT. Novice physical education teachers: experiences in initial teaching education. Objective: To present the experiences and living, graduating experiences contributions of the initial academic formation and experiences of professional development of six beginning teachers, graduating from a Physical Education course. Methods: The study has a qualitative character of descriptive way with approach and transversal design. An interview was used in data collection, with content analysis treatment. Results: The main results show the appreciation of the disciplines of educational training and pedagogical training, discrepancies between training and school context and the influence of adverse situations as challenging elements at the beginning of teaching. The motivation and desire to remain in the profession reveal elements of positive perception of professional effectiveness. Conclusion: It is concluded that teachers perceive as meaningful the experiences of academic life, feel motivated to teach, although the challenge of experiencing the shock of reality. We suggest the approximation of the initial formation with the context of the teaching, the pedagogical support at the beginning of the career with the objective of contributing to the professional development in a continuous sense.